Assertiveness and Self-Esteem among Nursing Students of Manipal College of Medical Science of Pokhara, Nepal - Shrestha, Sandhya (Journal of Chitwan Medical College, 2019)
Background: Assertive behaviour and low self-esteem have been found to major problem in the nursing profession. Nursing students today are the backbone of professional nurses of tomorrow. In order to ensure competent and safe practice, it is necessary for them to be individuals with high assertive skills and self-esteem. This study was conducted to identify assertiveness and self-esteem among nursing students. Methods: A descriptive cross sectional survey was conducted among 202 Proficiency Certificate Level and Bachelor of Science in nursing students of Manipal College of Medical Sciences (nursing programme), Pokhara, Nepal during July/August 2015. Data collection was done by purposive sampling. Tools used were demographic proforma, Begley and Glacken Assertiveness behavior questionnaire and Rosenberg self-esteem scale. Data were analyzed using descriptive and inferential statistics chi-square and correlation coefficient. Results: The study revealed nursing students had moderate level of assertiveness and self-esteem. There is a significant association between assertiveness and level of study and residence. There is a significant association between level of self-esteem with level of study and residence and There is significant positive correlation (r= 412) among assertiveness and self-esteem score with p value <0.001. Conclusion: It is concluded that majority of nursing students have moderate assertiveness and self–esteem. Nurse educators should take initiation to improve high assertiveness and self-esteem of nursing students.